Colorimetric and fluorescence "turn-on" recognition of fluoride by a maleonitrile-based uranyl salen-complex. (December 2016) - Bartocci, Silvia; Sabaté, Ferran; Bosque, Ramon; Keymeulen, Flore; Bartik, Kristin; Rodríguez, Laura; Dalla Cort, Antonella
Abstract: The synthesis and characterization of two new uranyl-salen complexes, 1 –2, based on a 1, 2-diaminomaleonitrile unit, is described. Spectroscopic studies to evaluate their potential as colorimetric probes for fluoride detection in chloroform and dichloromethane were undertaken. Compound2 exhibits a 'turn-on' response characterized by a naked-eye colorimetric change for the selective recognition of fluoride in both solvents. DFT calculations show that the stabilization energy for the formation of the host:guest complex follows the trend F − > Cl − > Br − hence supporting the experimental data. Graphical abstract: Highlights: Two new uranyl-salen complexes based on a 1, 2-diaminomaleonitrile are described. Spectroscopic studies proof their potential use for fluoride detection. The presence of two bulky substituents favors the molecular recognition process. DFT calculations support the experimental data.